2017
DOI: 10.15537/smj.2017.11.21119
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulonephritis disease pattern at Saudi tertiary care center

Abstract: Objective:To assess changes in the pattern of glomerular diseases to help guide optimal allocation of resources, to focus future reasearch, and improve outcomes.Methods:A retrospective chart review was conducted on kidney biopsies taken between 2007 and 2016 at a single tertiary care center in Saudi Arabia (King Fahad Medical City, Riyadh) to evaluate the prevalence and pattern of glomerulonephritis (GN).Results:The most common primary GN in 102 biopsies from adult patients with a mean age of 28.9 ± 13.6 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
8
10
0
Order By: Relevance
“…Interestingly, the majority of SLE adult patients were also class IV LN. 10 In our cohort, a high titre of ANA was significantly associated with higher disease activity, consistent with previous studies. 11 However, a high titre of anti-dsDNA showed an insignificant pattern (1:80; p =0.052) of association with a higher SLEDAI score.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the majority of SLE adult patients were also class IV LN. 10 In our cohort, a high titre of ANA was significantly associated with higher disease activity, consistent with previous studies. 11 However, a high titre of anti-dsDNA showed an insignificant pattern (1:80; p =0.052) of association with a higher SLEDAI score.…”
Section: Discussionsupporting
confidence: 93%
“…MPGN and mesangial proliferative GN were each reported in 4.3% of our patients, and these were less prevalent in our cohort compared with that in earlier studies [ 8 – 10 ] owing to an improved infection control; similar results have been reported in recent data from Saudi Arabia [ 22 ] and Dubai [ 21 ].…”
Section: Methodssupporting
confidence: 89%
“…FSGS was reported as the predominant pattern of GN in a previous report from Jordan [ 8 ]; however, it was less prevalent in our study. It is still the most common type of primary GN in Saudi Arabia [ 22 ] and Iran [ 23 ] and the second most common type of primary GN in the United States of America [ 11 ]. FSGS prevalence was underestimated in our study because of the clinical indications of kidney biopsy, changes in nephrologist's practice with advanced renal impairment in the presence of proteinuria and hypertension, and absence of renal disease screening strategies.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to these findings, a recent local publication on data from all renal biopsies identified PLN in 51 out of 63 biopsies with LN, of which 59% were class IV. 35 In a larger local cohort study ( n = 226), among all biopsies with PLN, class IV was found in 69%, class III in 19% and mixed PLN in 12%. 9,10…”
Section: Discussionmentioning
confidence: 93%